The Battle of Manzikert and Its Role in the Crusades (463 AH / 1071 AD) - Al-Sarhan, Khader Eid Mufleh; Al-Zawahra, Muntaser Khalifa Falah (The Algerian Historical Journal, 2026)
This research explores one of the most prominent battles during the Seljuk era -the Battle of Manzikert-, which took place in 463 AH / 1071 AD, during the reign of Sultan Alp Arslan. The conflict between the Byzantine Empire and the Seljuk state had reached its peak during this period. The study introduces the location of the battle and the reason behind its name, examines the causes and motivations that led to the outbreak of the conflict from both perspectives, and outlines the course and events of the battle. It also presents the conclusions reached by the research.